2021
DOI: 10.3390/su13116330
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions of Stationary Battery Installations in Two Renewable Energy Projects

Abstract: The goal to decrease greenhouse gas (GHG) emissions is spurring interest in renewable energy systems from time-varying sources (e.g., photovoltaics, wind) and these can require batteries to help load balancing. However, the batteries themselves add additional GHG emissions to the electricity system in all its life cycle phases. This article begins by investigating the GHG emissions for the manufacturing of two stationary lithium-ion batteries, comparing production in Europe, US and China. Next, we analyze how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Specific emission values for lithium-ion batteries vary greatly in the literature and depend on the manufacturing location. The current values range approximately 80-250 kg CO 2 -eq/kWh [45,46], and similarly, broad ranges are present in the PV and heat storage values. Therefore, sensitivity from the life cycle emission factors was assessed by varying the emission factors of all components, as in Table 7.…”
Section: Feasibility Of Component Life Cycle Emissionsmentioning
confidence: 76%
“…Specific emission values for lithium-ion batteries vary greatly in the literature and depend on the manufacturing location. The current values range approximately 80-250 kg CO 2 -eq/kWh [45,46], and similarly, broad ranges are present in the PV and heat storage values. Therefore, sensitivity from the life cycle emission factors was assessed by varying the emission factors of all components, as in Table 7.…”
Section: Feasibility Of Component Life Cycle Emissionsmentioning
confidence: 76%
“…Table 5. Equivalent CO2 emissions per kWh for each source Main grid PV WT BESS kg CO2 eq/kWh 1.06 [37] 0 0 0…”
Section: Carbon Dioxide Emissionsmentioning
confidence: 99%
“…Assuming that a future official PED definition will include a net-zero emission balance, an allowable limit of GHG emissions per unit of generated/consumed thermal/electrical energy will also gain importance in technology choice. Pucker et al [26], for example, showed that storage solutions to increase the self-sufficiency in decentralized renewable energy systems not always reduce GHG emissions due to embodied emissions, but also due to direct emissions caused by the energy needed to produce and operate the devices as well as the related losses. Thus, renewable energy sources and technology portfolios have to be selected based on a number of factors: local climate, market and regulatory conditions (e.g., on energy transactions), the ability for multi-use applications, the onsite building characteristics in order to match building load profiles and renewable energy sources and, finally, direct and indirect GHG emissions.…”
Section: Technology Outlook For Pebs and Peds In The Energy Community Contextmentioning
confidence: 99%